Development of a Ball Track Learning Medium to Enhance Early Childhood Attention: Pengembangan Media Jalur Bola untuk Melatih Fokus Anak Usia Dini - Salsabila Fadhilatusy Syifa; Mierrina Mierrina (Bestari: Jurnal Pendidikan dan Kebudayaan, 2026)
Focus is a crucial skill in early childhood that influences children’s cognitive, social, and emotional development. However, many children at this stage struggle to maintain attention for an extended period. This study aims to develop and examine the effectiveness of the ball track game as a medium to improve focus in early childhood. The research employed a research and development method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The subjects were young children participating in a limited trial, while the instruments consisted of expert validation sheets and behavioral observations. The findings indicate that the ball track game is feasible as a learning medium and provides positive impacts on children’s focus, motor coordination, and problem-solving skills. This medium integrates play and learning in an engaging way, making children more enthusiastic and motivated. Therefore, the ball track game can serve as an innovative alternative in early childhood education to support the development of concentration from an early age.